2016
DOI: 10.1093/mmy/myw090
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of azole-resistantAspergillus fumigatusin the environment of Thailand

Abstract: Occurrence of azole-resistant Aspergillus fumigatus (ARAF) in the environment is an emerging problem worldwide, likely impacting on patient treatment. Several resistance mutations are thought to have initially arisen through triazole-based fungicide use in agriculture and subsequently being propagated in a similar manner. Here we investigated the prevalence of ARAF in the environment of Thailand and characterized their susceptibility profiles toward clinically used azole compounds along with underlying resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
2
34
3
Order By: Relevance
“…The isolates carrying TR 46 /Y121F/T289A allele were grouped into four csp1 subtypes: t01 (1/6), t02 (3/6), t09 (1/6) and t18 (1/6). The control isolate Af293, which was isolated from a patient with invasive aspergillosis belonged to csp1 subtype t06 and the azole resistant control isolate BUU09 belonged to the t04B csp1 subtype, which agreed with previously published results (24).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The isolates carrying TR 46 /Y121F/T289A allele were grouped into four csp1 subtypes: t01 (1/6), t02 (3/6), t09 (1/6) and t18 (1/6). The control isolate Af293, which was isolated from a patient with invasive aspergillosis belonged to csp1 subtype t06 and the azole resistant control isolate BUU09 belonged to the t04B csp1 subtype, which agreed with previously published results (24).…”
Section: Resultssupporting
confidence: 91%
“…Prevalence of AR Af in the UK was found to be lower than that of other European countries and Colombia (15, 17, 2529), but higher than most Asian countries (24, 3033), with the exception of India (29, 34). Our findings are also in close agreement with a recent UK-based environmental prevalence study in Wales, where AR Af was detected in 4.5% (30/671) of soil samples, with resistance predominantly found in urban city locations (13).…”
Section: Discussionmentioning
confidence: 67%
“…Prevalence of ARAf in the UK was found to be lower than that of other European countries and Colombia (16,18,(25)(26)(27)(28)(29) but higher than most Asian countries (24,(30)(31)(32)(33), with the exception of India (29,34). Our findings are also in close agreement with a recent UK-based environmental prevalence study in Wales, where ARAf was detected in 4.5% (30/671) of soil samples, with resistance predominantly found in urban city locations (14).…”
Section: Discussionsupporting
confidence: 91%
“…Another study compared the prevalence and CYP51A mutations of clinical and environmental ARAF in different geographic areas of Germany and found a higher prevalence of TR 34 /L98H and TR 46 /Y121F/T289A isolates in the environment than in clinical isolates (4%‐15% vs 0%‐3%), whereas some other mutations, such as G54W or M220L, were only present in clinical isolates . Furthermore, except a study in which TR 46 /Y121F/T289A isolates were found in the home of patient with IA, and another one assessing eight domiciles in the Netherlands, most environmental ARAF were isolated from soil or outdoor/indoor air samples in hospitals …”
Section: Introductionmentioning
confidence: 99%
“…20 Furthermore, except a study in which TR 46 /Y121F/ T289A isolates were found in the home of patient with IA, 19 and another one assessing eight domiciles in the Netherlands, 21 most environmental ARAF were isolated from soil or outdoor/indoor air samples in hospitals. [22][23][24][25] In this study, we aimed to determine the prevalence of ARAF in azole-naïve COPD patients and their homes, and assess whether CYP51A mutations of ARAF isolates were similar in clinical and environmental reservoirs, in order to evaluate if the domestic mold environmental exposure could be a risk factor for the acquisition of ARAF isolates in these patients.…”
Section: Introductionmentioning
confidence: 99%